Imaging Extracellular Lactate In Vitro and In Vivo Using CEST MRI and a Paramagnetic Shift Reagent. Issue 8 (12th January 2017) - Zhang, Lei; Martins, André F.; Mai, Yuyan; Zhao, Piyu; Funk, Alexander M.; Clavijo Jordan, M. Veronica; Zhang, Shanrong; Chen, Wei; Wu, Yunkou; Sherry, A. Dean
Abstract: Overproduction of lactate is a hallmark of cancer, yet a method to quantitatively measure lactate production by cancer cells is not straight‐forward. Chemical exchange saturation transfer magnetic resonance imaging (CEST MRI) can potentially be used to image lactate but the small difference in chemical shift of the lactate −OH proton and water proton resonances make it challenging. Like other spectroscopic methods, CEST MRI cannot discriminate intracellular lactate from extracellular lactate. Herein, we demonstrate a relatively simple way to shift the lactate −OH proton resonance far away from water by addition of the paramagnetic shift reagent, EuDO3A, while retaining the CEST properties of lactate itself. The potential of the method was demonstrated by imaging extracellular lactate excreted from lung cancer cells in tissue culture without interference from other components in the culture media and by imaging excess lactate excreted into the bladder of a mouse. Abstract : Looking for lactate : A simple chemical exchange saturation transfer (CEST) method is demonstrated for imaging lactate by using of a paramagnetic shift reagent (SR) to shift the lactate −OH CEST peak well downfield of water. This feature enables direct MR imaging of extracellular lactate produced by cancer cells in cultures and the lactate⋅EuDO3A complex in vivo.